Hantavirus inhibits apoptosis by preventing mitochondrial membrane potential loss through up-regulation of the pro-survival factor BCL-2 - Solà-Riera, Carles; García, Marina; Ljunggren, Hans-Gustaf; Klingström, Jonas (PLoS pathogens, 2020)
Hantaviruses, zoonotic RNA viruses belonging to the order Bunyavirales, cause two severe acute diseases in humans, hemorrhagic fever with renal syndrome (HFRS) and hantavirus pulmonary syndrome (HPS). Hantavirus-infected patients show strong cytotoxic lymphocyte responses and hyperinflammation; however, infected cells remain mostly intact. Hantaviruses were recently shown to inhibit apoptosis in infected cells. By inhibiting granzyme B- and TRAIL-mediated apoptosis, hantaviruses specifically and efficiently inhibit cytotoxic lymphocyte-mediated killing of infected cells. Hantaviruses also strongly inhibit apoptosis triggered intrinsically; i.e., initiated through intracellular activation pathways different from those used by cytotoxic lymphocytes. However, insights into the latter mechanisms are currently largely unknown. Here, we dissected the mechanism behind how hantavirus infection, represented by the HFRS-causing Hantaan virus and the HPS-causing Andes virus, results in resistance to staurosporine-induced apoptosis. Less active caspase-8 and caspase-9, and consequently less active caspase-3, was observed in infected compared to uninfected staurosporine-exposed cells. While staurosporine-exposed uninfected cells showed massive release of pro-apoptotic cytochrome C into the cytosol, this was not observed in infected cells. Further, hantaviruses prevented activation of BAX and mitochondrial outer membrane permeabilization (MOMP). In parallel, a significant increase in levels of the pro-survival factor BCL-2 was observed in hantavirus-infected cells. Importantly, direct inhibition of BCL-2 by the inhibitor ABT-737, as well as silencing of BCL-2 by siRNA, resulted in apoptosis in staurosporine-exposed hantavirus-infected cells. Overall, we here provide a tentative mechanism by which hantaviruses protect infected cells from intrinsic apoptosis at the mitochondrial level by inducing an increased expression of the pro-survival factor BCL-2, thereby preventing MOMPs and subsequent activation of caspases. The variety of mechanisms used by hantaviruses to ensure survival of infected cells likely contribute to the persistent infection in natural hosts and may play a role in immunopathogenesis of HFRS and HPS in humans.